2021
DOI: 10.1177/08258597211045500
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and Depressive Symptoms in Elderly Palliative Care Patients

Abstract: Objective: The aim of this study is to determine the prevalence of and relationship between malnutrition and depressive symptoms in older palliative care inpatients. Methods: One hundred and thirty-six older adults were included in the study. The Geriatric Depression Scale, Mini Nutritional Assessment Short Form, Mini Mental State Examination, Barthel index, and Lawton & Brody index were used to evaluate the mood, nutrition status, mental status, and activities of daily living of the patients. Results: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In a recent study including 319 patients in our country, patients receiving palliative care were screened according to the nutrition risk screening 2002 and malnutrition was detected in 58.6% of the patients [23]. Another study conducted among 136 geriatric palliative care patients in our country showed that 39.7% of the patients had malnutrition and 47.1% were at risk of malnutrition [24]. In studies conducted among patients receiving long-term care, this rate varied widely between 12.5% and 78.9% [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study including 319 patients in our country, patients receiving palliative care were screened according to the nutrition risk screening 2002 and malnutrition was detected in 58.6% of the patients [23]. Another study conducted among 136 geriatric palliative care patients in our country showed that 39.7% of the patients had malnutrition and 47.1% were at risk of malnutrition [24]. In studies conducted among patients receiving long-term care, this rate varied widely between 12.5% and 78.9% [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the daily caloric needs of the patients followed up in our palliative care center, it is aimed to provide carbohydrate, protein, fat, essential amino acid, vitamin, and mineral balances by considering their accompanying co-morbidities and laboratory findings (16). It has been shown that meeting adequate nutritional needs is effective in increasing the quality of life in elderly individuals and in preventing depression (17). Even when our patients' daily needs were calculated (18), it was observed that most of the patients could tolerate only 50%-75% of that.…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition, risk of malnutrition, and depressive symptoms often occur among patients, and the relationship between them was statistically significant. Thus, the quality of life of cancer patients could be improved by providing adequate nutrition and psychological support [15]. The functional consequences of malnutrition not only cause physical changes but also psychological changes such as depression, anxiety, irritability, apathy, poor sleep patterns, and loss of concentration [16].…”
Section: Introductionmentioning
confidence: 99%